The Effect of Stimulus Duration and Motor Response in Hemispatial Neglect during a Visual Search Task - Jelsone-Swain, Laura M. (Public Library of Science, 2012)
Patients with hemispatial neglect exhibit a myriad of profound deficits. A hallmark of this syndrome is the patients' absence of awareness of items located in their contralesional space. Many studies, however, have demonstrated that neglect patients exhibit some level of processing of these neglected items. It has been suggested that unconscious processing of neglected information may manifest as a fast denial. This theory of fast denial proposes that neglected stimuli are detected in the same way as non-neglected stimuli, but without overt awareness. We evaluated the fast denial theory by conducting two separate visual search task experiments, each differing by the duration of stimulus presentation. Specifically, in Experiment 1 each stimulus remained in the participants' visual field until a response was made. In Experiment 2 each stimulus was presented for only a brief duration. We further evaluated the fast denial theory by comparing verbal to motor task responses in each experiment. Overall, our results from both experiments and tasks showed no evidence for the presence of implicit knowledge of neglected stimuli. Instead, patients with neglect responded the same when they neglected stimuli as when they correctly reported stimulus absence. These findings thus cast doubt on the concept of the fast denial theory and its consequent implications for non-conscious processing. Importantly, our study demonstrated that the only behavior affected was during conscious detection of ipsilesional stimuli. Specifically, patients were slower to detect stimuli in Experiment 1 compared to Experiment 2, suggesting a duration effect occurred during conscious processing of information. Additionally, reaction time and accuracy were similar when reporting verbally versus motorically. These results provide new insights into the perceptual deficits associated with neglect and further support other work that falsifies the fast denial account of non-conscious processing in hemispatial visual neglect.